Today’s Sigma Generation Society: The Future Influenced by Social Media - Madraximov Alisher Usubjon Ugli (Web of Scientist International Scientific Research Journal, 2025)
study explores the emergence of the "Sigma Generation," a social category shaped by digital technologies and social media. The research investigates the psychological and sociological characteristics of Sigma individuals and their impact on modern society. A qualitative research approach, including content analysis and comparative studies, is used to understand the evolution of digital identity. The results highlight the increasing influence of online interactions in shaping individual behavior, leading to shifts in social structures and interpersonal relationships